2017
DOI: 10.1080/24725854.2017.1299956
|View full text |Cite
|
Sign up to set email alerts
|

Shewhart control charts for dispersion adjusted for parameter estimation

Abstract: Shewhart control charts for dispersion adjusted for parameter estimationGoedhart, R.; da Silva, M.M.; Schoonhoven, M.; Epprecht, E.K.; Chakraborti, S.; Does, R.J.M.M.; Veiga , A. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 24 publications
(47 reference statements)
0
29
0
Order By: Relevance
“…However, there is some concern about the deterioration in the OOC CARL performance relative to using the unadjusted limits which are wider. This is of course true for all types of control charts with estimated parameters and has been observed, for example, for the Shewhart charts (see Goedhart et al). The extent of the deterioration depends on the size of the shift δ and m .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, there is some concern about the deterioration in the OOC CARL performance relative to using the unadjusted limits which are wider. This is of course true for all types of control charts with estimated parameters and has been observed, for example, for the Shewhart charts (see Goedhart et al). The extent of the deterioration depends on the size of the shift δ and m .…”
Section: Discussionmentioning
confidence: 63%
“…This improved IC performance, that is widening the limits, can lead to some deterioration of the OOC chart performance. This has been noted in the literature (see, eg, Goedhart et al) as the price to pay for satisfactory nominal IC chart performance with a high probability. However, it is possible with our approach to relax the IC behavior of the EWMA chart.…”
Section: Adjustment Of the Standard Phase II Ewma Chart Limits For Gumentioning
confidence: 91%
“…The utilization of auxiliary information at estimation stage and imposing the restrictive assumptions of known process parameters do not seem realistic practically. The drawbacks of the assumption of known process parameters can be viewed in the studies of Schoonhoven et al, Schoonhoven and Does, Diko et al, Goedhart et al, Haridy et al, and Jensen et al…”
Section: Introductionmentioning
confidence: 99%
“…The results have shown that the analytical and the bootstrap approaches get similar performance by efficiently adjusting the control limits of the chart. To monitor the process variance, some studies were also conducted on the Shewhart S2 chart; readers may refer to Faraz et al and Goedhart et al All the above studies focused on the conditional properties of control charts with unknown process parameters. General results showed that an impractically large number of phase I data is needed when a practitioner wants to have his(her) own chart's in‐control properties close to the desired one.…”
Section: Introductionmentioning
confidence: 99%